Spring-Powered Needle-Free Injection of Triamcinolone Acetonide and 5-Fluorouracil for Keloid Treatment - Sutedja EK; Sundani A; Ruchiatan K; Sutedja E (Dove Medical Press, 2023)
Eva Krishna Sutedja, Annisa Sundani, Kartika Ruchiatan, Endang Sutedja Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, West Java, IndonesiaCorrespondence: Eva Krishna Sutedja, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel/Fax +62 222032426 ext 3449, Email evakrishna@yahoo.comIntroduction: Keloid is an abnormal fibroproliferative healing response characterized by excessive and invasive tissue growth beyond the wound boundaries. The conventional treatment involves injecting drugs such as triamcinolone acetonide (TA), 5-fluorouracil (5-FU), or their combination intralesionally. However, the pain associated with injections often leads to low patient compliance and treatment failure. The spring-powered needle-free injector (NFI) provides an affordable alternative option for drug delivery with reduced pain.Case: This case report presents a 69-year-old female patient with a keloid treated using a spring-powered needle-free injector (NFI) for drug delivery. The keloid was assessed using the Vancouver Scar Scale (VSS) and the Patient and Observer Scar Assessment Scale (POSAS). The patient's pain level was measured using the Numeric Pain Rating Scale (NPRS). TA and 5-FU mixed with lidocaine were loaded into the NFI and injected at a dose of 0.1 mL/cm2. The treatment was repeated twice a week. After four sessions, the keloid flattened by 0.5 cm, VSS score decreased from 11 to 10, and POSAS scores decreased from 49 to 43 (observer) and from 50 to 37 (patient). The NPRS during each procedure was 1, indicating minimal pain.Discussion: The spring-powered NFI is a simple and cost-effective device that operates based on Hooke's law, producing a high-pressure fluid jet for effective skin penetration. The NFI demonstrated effectiveness in treating keloid lesions, resulting in visible improvement after four treatments.Conclusion: The spring-powered NFI offers an affordable and painless alternative to keloid treatment.Keywords: 5-fluorouracil, keloid treatment, needle-free injection, spring-powered, triamcinolone acetonide